Selection of drive system and chassis structure basic design and analysis for medium-sized urban electric bus - Naufal Aflah Hibatullah; Rachman Setiawan (Politeknik Negeri Lhokseumawe, 2024)
One of the alternative solutions to address environmental and energy challenges is the utilization of electric vehicles, particularly in the domain of public transportation. The focus was on the development of medium-sized electric buses to expand the reach of electric-powered public transport. The design process encompasses the selection of vehicle components, such as the drive system, and the configuration of a space frame chassis structure. The drive system was meticulously chosen and proved to exceed the design requirements, as it achieved a gradability of 12.44%, surpassing the targeted capability of 10% slope. Moreover, it boasts a maximum speed of 108 km/h, exceeding the design requirement of a maximum speed of 50 km/h, and can accelerate at a rate of 1-2 m/s². The chassis design adheres to regulations and standards and is grounded in the strength, stiffness, and natural frequency criteria. The initial chassis design did not meet the design requirement, however, through several iterations, a chassis structure was achieved with a vertical bending stiffness of 8.57 kN/mm and a torsional stiffness of 9.63 kNm/°. Based on the outcomes of this research, a drive system and chassis structure design that fully satisfies all the existing design requirements has been successfully attained.